2021
DOI: 10.1152/ajpendo.00412.2020
|View full text |Cite
|
Sign up to set email alerts
|

Mild stimulatory effect of a probiotic mix on bone mass when treatment is initiated 1.5 weeks after ovariectomy in mice

Abstract: Studies in humans and rodents show that probiotic bacteria can protect from bone loss caused by sex-steroid deficiency. We showed earlier that a mixture of three probiotic bacteria, Lacticaseibacillus paracasei DSM13434, Lactiplantibacillus plantarum DSM 15312 and DSM 15313 (L. Mix) protects mice from ovariectomy (ovx)-induced bone loss when treatment was started two weeks before sham and ovx surgery. In addition, the same probiotic treatment protected against lumbar spine bone loss in early postmenopausal wom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Mix, we saw a protective effect on bone but no effect on body weight with L . Mix ( Ohlsson et al 2014 , 2021 ). However, the effect of castration on body composition is completely different for male and female mice.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Mix, we saw a protective effect on bone but no effect on body weight with L . Mix ( Ohlsson et al 2014 , 2021 ). However, the effect of castration on body composition is completely different for male and female mice.…”
Section: Discussionmentioning
confidence: 99%
“…Teklad diet 2016 does not contain alfalfa or soybean meal, thus minimizing the occurrence of natural phytoestrogens that can interfere in studies of castration-induced bone loss. We made the decision to use the C57BL/6J mouse strain since we used this strain in earlier studies of the effect of probiotic bacteria on castration-induced bone loss and wanted to be able to compare the results ( Ohlsson et al 2014 , 2021 , Lawenius et al 2020 , 2022 ). At 12 weeks of age, the mice were randomized into four groups ( n = 13–15) and subjected to orx or sham surgery under inhalation anesthesia with isoflurane (Baxter Medical AB, Kista, Sweden).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The therapeutic use of gut microbes as a target for skeletal diseases has become a current hot topic. Gut microbial dysbiosis is one of the important pathogenic mechanisms underlying primary osteoporosis, and several therapies based on gut microbes are used to alleviate primary osteoporosis ( Ohlsson and Sjögren, 2015 ), such as antibiotics ( Cox et al., 2014 ), probiotics ( Ohlsson et al., 2021 ), prebiotics (oligosaccharides and polysaccharides) ( Porwal et al., 2020 ; Zhang et al., 2021 ), and faecal bacteria transplants ( Ding et al., 2020 ). From the perspective of the gut microbes, which are beneficial to bone health, some studies have found that external factors, as a novel approach, could intervene in the composition of the gut microbes to increase beneficial bacteria and reduce the abundance of bacteria that are detrimental to bone health, and subsequently influence bone metabolism and bone mass changes.…”
Section: Interventions With Specific Gut Microbiota To Improve Bone H...mentioning
confidence: 99%